Le tre costituzioni pacifiste Il rifiuto della guerra nelle costituzioni di Giappone, Italia e Germania - Losano, Mario G. (Global Perspectives on Legal History, 2020)
The three defeated Axis powers - Japan, Italy and Germany - incorporated a prohibition on wars of aggression into their democratic constitutions. This book covers the years of the Nuremberg and Tokyo Trials and the constituent assemblies of 1947- 49 through to current debates on the adaptation of the pacifi st articles in line with new "humanitarian" wars. Aspects relating to the birth of the three countries' constitutions are treated in great detail in three appendices.